PERLINDUNGAN HUKUM TERHADAP PASIEN RAWAT INAP BERDASARKAN UNDANG-UNDANG NOMOR 44 TAHUN 2009 TENTANG RUMAH SAKIT - Arif Awangga (LPPM STIH Awang Long, 2023)
Legal protection means recognition, compliance, and support for the rights of all individuals, all families and all groups, as well as aspects of their implementation. Thus, patient protection law is the entirety of the principles and rules that regulate and protect patients in the relationship and problems of medical services with medical personnel and medical providers, in terms of obtaining medical services. Legal protection is a protection given to legal subjects, namely individuals or legal entities in the form of tools, both preventive and repressive, both oral and written. In Law No. 44 of 2009 concerning Hospitals Article 1 Regarding General Provisions, it is a health service institution that provides complete individual health services that provide inpatient, outpatient, and emergency services.